1998
DOI: 10.1007/s004420050469
|View full text |Cite
|
Sign up to set email alerts
|

The influence of elevated CO 2 and O 3 concentrations on Scots pine needles: changes in starch and secondary metabolites over three exposure years

Abstract: Scots pine (Pinus sylvestris L.) trees, aged about 20 years old, growing on a natural pine heath were exposed to two concentrations of CO (ambient CO and double-ambient CO) and two O regimes (ambient O and double-ambient O) and their combination in open-top chambers during growing seasons 1994, 1995 and 1996. Concentrations of foliar starch and secondary compounds are reported in this paper. Starch concentrations remained unaffected by elevated CO and/or O concentrations during the first 2 study years. But in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 44 publications
(54 reference statements)
2
48
1
Order By: Relevance
“…In white birch (Betula pendula Roth) grown at 20°C above ambient, while total foliar HPLC phenolics decreased, flavone aglycones increased (Kuokkanen et al 2001). Previous studies report that monoterpene pool sizes in conifer tissues either increase (Heyworth et al 1998), decrease (Williams et al 1994) or do not change (Roth and Lindroth 1994;Kainulainen et al 1998) in response to growth at elevated CO 2 . The reasons for the decline in monoterpene concentration in the current study at higher CO 2 availability are not clear.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In white birch (Betula pendula Roth) grown at 20°C above ambient, while total foliar HPLC phenolics decreased, flavone aglycones increased (Kuokkanen et al 2001). Previous studies report that monoterpene pool sizes in conifer tissues either increase (Heyworth et al 1998), decrease (Williams et al 1994) or do not change (Roth and Lindroth 1994;Kainulainen et al 1998) in response to growth at elevated CO 2 . The reasons for the decline in monoterpene concentration in the current study at higher CO 2 availability are not clear.…”
Section: Discussionmentioning
confidence: 97%
“…Growth at elevated CO 2 , and/or low nutrient availability, typically increases the amount of carbon in woody plant tissues that is in excess of that required for immediate growth (Griffin et al 1996;Kelsey et al 1998). Yet, monoterpene pool sizes in conifer tissues either increase (Heyworth et al 1998), decrease (Williams et al 1994) or do not change (Roth and Lindroth 1994;Kainulainen et al 1998;Constable et al 1999) in response to growth at elevated CO 2 . Similarly, monoterpene pools in conifer needles reportedly increase (Kainulainen et al 1996), decrease (Bjorkman et al 1991McCullough and Kulman 1991), or do not change (Holopainen et al 1995) in response to reduced growth caused by nitrogen deficiency.…”
Section: Introductionmentioning
confidence: 97%
“…Elevation of growth temperature has been found to decrease (Snow et al 2003) or have no effect (Constable et al 1999) on the monoterpene concentration in needles of Douglas fir but increase the concentration in Scots pine (Sallas et al 2003). The concentration of total phenolics in Scots pine needles have shown no significant change in response to elevation of CO 2 or temperature or their interaction (Kainulainen et al 1998;Sallas et al 2003).…”
Section: Introductionmentioning
confidence: 93%
“…The effect of increased CO 2 and concomitant increase in temperature on terpenoids and phenolics are quite variable depending on the studied plant species, age and the duration of the exposure (reviewed by Peñuelas and Estiarte 1998). Monoterpene levels in the needles of Douglas fir (Snow et al 2003;Litvak et al 2002) and Scots pine (Sallas et al 2003) have been reported to reduce due to elevated CO 2 , but then again no significant effect has been found in other studies with Douglas fir, Ponderosa pine (Constable et al 1999) or Scots pine (Kainulainen et al 1998). The effect of elevated temperature on the monoterpene pool size is equally unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Ozone exposure has been shown to increase conifer phenolic concentrations, 117 but low ozone exposure had no effect on monoterpene and resin acid concentrations. 118 Changes in crop quality due to ozone exposure have been studied in a limited number of crops. For example, in wheat, ozone reduced yield but increased grain protein concentration.…”
Section: Influence Of Climate Change On Secondary Metabolitesmentioning
confidence: 99%